Detecting clinical activity in systemic lupus erythematosus with an archaeal poly(ADP-ribose) polymerase-like thermozyme: a pivotal study - Faraone-Mennella, Maria Rosaria; Scarpa, Raffaele; Petrella, Anna; Manguso, Francesco; Peluso, Rosario; Farina, Benedetta (Biomarkers, 2009)
The clinical usefulness of an immunotest was evaluated by using purified poly(adenosine diphosphate (ADP)-ribose) polymerase from Sulfolobus solfataricus (PARPSso) as an antigen to detect the presence of abnormal anti-PARP antibodies in the sera of patients with systemic lupus erythematosus (SLE) at different clinical stages. Sera from 44 patients with SLE, subgrouped on the basis of disease activity (16 with inactive disease, 28 with active disease) were analysed with a new immunotest to detect anti-PARP antibodies, and with an immunofluorescent (IIF) assay for antinuclear antibodies (ANA) detection. ANA detection by IIF revealed that sera of healthy subjects were negative, whereas sera from patients with SLE were positive in all cases (13 positive at 1:80, 15 at 1:160, 15 at 1:320, 1 at 1:640, v/v). Anti-PARP activity was higher in ANA-positive patients than in controls (p = 0.005). Within the group of SLE sera, disease and anti-PARP activity was increased more significantly in patients with active than in those with inactive disease (p < 0.001 and p = 0.001, respectively). Correlation between anti-PARP and disease activity in SLE patients was statistically significant (p < 0.001). PARPSso seems to be suitable for detecting anti-PARP antibodies and could play a role as a serological marker of disease activity in patients with SLE.